The evaluative teaching practices and the formation of socialimaginaries in primary school teachers, school Our Lady ofBethlehem - Torres Cadena, Nelson Enrique (Universidad Francisco de Paula Santander, 2017)
The present article reports on a research that proposed as a general objective to establish whether or notthere is a relationship between teacher evaluation practices and the way in which they influence the creation of socialimaginaries. For the development of the research, a qualitative methodology was taken into account, for which threeinstruments were used: a semi-structured interview applied to teachers, a classroom observation and a student survey.In order to analyze the information, a categorization and triangulation process was carried out, making use of the Atlas. ti software .It was concluded that the evaluation processes arestilltraditionaland that,although there is repeated talk of integral evaluation, it continues to focus on the cognitive. Similarly, in terms of the general objective, to knowif there is a relationship between the form of evaluation, teachers avoid the question and recognize that many of their practices are influenced by the way they were evaluated,but at no time do they recognize that their for mofevaluation can contribute to students changing their view of the world